Teaching Electromagnetic Wave Simulation: Applying Perfectly Matched Layer (PML) in Two-Dimensional Fields - Arifin, Fikrul Ihsan; Alisati, Nayla Ananda Putri; Juliana, Amara (Current STEAM and Education Research, 2024)
Electromagnetic waves play a crucial role in various modern technological applications, such as wireless communication, radar, and signal processing. A deep understanding of the behavior of these waves in different media and boundary conditions can be achieved through numerical simulation. An in-depth understanding of electromagnetic wave behavior is essential in science and engineering education, in particular to help students visualize and analyze complex phenomena. This study discusses the two-dimensional (2D) simulation of electromagnetic waves using the Finite Difference Time-Domain (FDTD) method, with the implementation of Perfectly Matched Layer (PML) to address wave reflections at the simulation domain boundaries. Fundamental electromagnetic laws, such as Gauss's Law, Faraday's Law, and Ampere's Law, are used as the basis to develop the curl Maxwell equations in 2D. The proposed simulation algorithm calculates the electric fields (Ex, Ey) and magnetic field (Hz) considering the PML damping factor. Simulations are performed with various PML constant values (0.00001, 0.00005, 0.0001) to observe the effectiveness of wave absorption. The simulation results show that increasing the PML constant value reduces reflections and improves the accuracy of the simulation results. Therefore, the FDTD method integrated with PML is effective in modeling the behavior of electromagnetic waves in a 2D domain, providing more realistic and accurate results.